The Burden of Sleep/Wake Disorders: Excessive Daytime Sleepiness and Insomnia Project - Marina Tüzün; Ulf Kallweit; Stefan Seidel; Olga Endrich; Sven Trelle; Maurizio A. Leone; Oliviero Bruni; Richard Dodel; Maria Konti; Maria Lolich; Elisabetta Pupillo; Dauren Ramankulov; et al. (Methods and Protocols, 2024)
Excessive daytime sleepiness (EDS) and insomnia (IN) complaints represent the most common sleep/wake disorders. Currently, the specific needs of these patients and their relatives, as well as the overall socio-economic burden of IN and EDS remains widely unexplored. This pilot study to be carried out in Switzerland is a retro- and prospective, national, one-center cohort observational study for the systematic evaluation of the burden of EDS and IN and its evolution 12 months after the first assessment. Patient recruitment will be organized through 7–8 primary care providers (primary/general care practitioners and pharmacies). Primary outcomes are the prevalence of EDS/IN in the primary care setting and the association between EDS/IN with health-related quality of life (QOL) as assessed with the established instruments. Secondary outcomes are the association between EDS/IN with the presence of comorbidities, number of injuries/accidents, and number of sick/leave days for the subgroup of working subjects. Calculation of direct per-patient costs will be undertaken to analyze the economic implications of sleep/wake disorders, providing valuable insights into the financial burden experienced by affected individuals within the healthcare system. This research will provide information on the feasibility of such a study and inform on aspects of the QOL most associated with EDS/IN. Based on this pilot project, a European multicenter study on the burden of sleep/wake disorders will be conducted by the European Academy of Neurology.